Phytochemical Test and Antibacterial Activity of Pranawija (Euchresta horsfieldii (Lesch.) Benn.) - Amalia Indah Prihantini; Krisnawati Krisnawati; Anita Apriliani Dwi Rahayu; Yosephin Martha Maria Anita Nugraheni; Gipi Samawandana (Jurnal Ilmu Kehutanan)
Euchresta horsfieldii is a medicinal plant known in West Nusa Tenggara and Bali as pranajiwa. This study investigated phytochemical analysis and antibacterial activity of roots, stems, leaves, and seeds of E. horsfieldii. The samples were analyzed for their antibacterial activity against Bacilus subtilis Inacc-B334, Staphylococccus aureus Inacc-B4, and Escherchia coli Inacc-B5. The phytochemistry result indicated that alkaloids was the most dominant constituent of E. horsfieldii as it was detected in all parts of the plant. GC-MS analysis of the stems, roots, and seeds showed mome inositol, sophoridane, and fatty acids such as palmitic acid and strearic acid as the main components. The roots had the most varied constituents with detection of alkaloids, tannins, flavonoids, saponins, and terpenoids. Further, antibacterial activity assay showed that the stems and roots had antibacterial activity against S. aureus Inacc-B4 and E. coli Inacc B-5, whereas the seeds had antibacterial activity against B. subtilis Inacc-B-334 and S. aureus InaccB4. The result of the present study supports the investigation on potentiality of E. horsfieldii as alternative source for antibacterial agents.